2017
DOI: 10.18632/oncotarget.21689
|View full text |Cite
|
Sign up to set email alerts
|

Shift in energy metabolism caused by glucocorticoids enhances the effect of cytotoxic anti-cancer drugs against acute lymphoblastic leukemia cells

Abstract: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy. Treatments include glucocorticoids (GCs) such as dexamethasone (Dex) and prednisolone, which may be of value when used alongside cytotoxic anti-cancer drugs. To predict therapeutic efficacy of GCs, their activity against ALL cells is usually examined prior to chemotherapy; however, few studies have examined their effects when used in combination with other drugs. The paradox is that cytotoxic anti-cancer drugs that are effective agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Moreover, higher glycolytic rates are involved in resistance to chemotherapeutic agents, like daunorubicin [89]. The mitochondrial energy machinery seems however to be intact, as these cells are able to shift from glycolysis to OXPHOS fueled by autophagy under stress condition like exposure to glucocorticoids [90]. T cell ALL, conversely, appear to be less glycolytic and more oxidative [91].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…Moreover, higher glycolytic rates are involved in resistance to chemotherapeutic agents, like daunorubicin [89]. The mitochondrial energy machinery seems however to be intact, as these cells are able to shift from glycolysis to OXPHOS fueled by autophagy under stress condition like exposure to glucocorticoids [90]. T cell ALL, conversely, appear to be less glycolytic and more oxidative [91].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…Interestingly, genes involved in energy metabolism were differentially spliced, particularly in T-ALL. GCs induce a metabolic shift from glycolysis towards oxidative phosphorylation and it is postulated that oxidative stress plays a central role in GC-induced apoptosis of leukemic cells [12,51]. We found that GC-resistant T-ALL cells display altered splicing (in particular intron retention) of multiple genes involved in oxidative phosphorylation, in particular components of ubiquinol-cytochrome c reductase and NADH dehydrogenase complex (which promotes DNA damage-induced apoptosis through the production of reactive oxygen species (ROS)) [51].…”
Section: Discussionmentioning
confidence: 99%
“…GCs induce a metabolic shift from glycolysis towards oxidative phosphorylation and it is postulated that oxidative stress plays a central role in GC-induced apoptosis of leukemic cells [12,51]. We found that GC-resistant T-ALL cells display altered splicing (in particular intron retention) of multiple genes involved in oxidative phosphorylation, in particular components of ubiquinol-cytochrome c reductase and NADH dehydrogenase complex (which promotes DNA damage-induced apoptosis through the production of reactive oxygen species (ROS)) [51]. As intron retention often results in premature stop codons and transcript degradation, these changes are likely to result in diminished GC-induced oxidative phosphorylation and, therefore, suppress the production of ROS and consequently apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…One such recent study profiled CCRF‐CEM clones exposed to dexamethasone alone or in combination with etoposide, an inhibitor of topoisomerase 2 that disrupts mitochondrial homeostasis, and other anticancer drugs. Three phenotypic subtypes emerged: (1) cells that were resistant to dexamethasone independent of etoposide treatment, (2) cells where an additive effect was observed (termed CEM‐ADD), (3) cells responsive to dexamethasone but with no observed synergy in the presence of etoposide (termed CEM‐NON) . Reduced glycolysis was measured in both CEM‐ADD and CEM‐NON, as judged by decreased lactate levels, decreased mRNA expression of glycolytic genes hexokinase 2 (HK2) and lactate dehydrogenase A (LDHA), and decreased protein expression of HK2 .…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…104 Reduced glycolysis was measured in both CEM-ADD and CEM-NON, as judged by decreased lactate levels, decreased mRNA expression of glycolytic genes hexokinase 2 (HK2) and lactate dehydrogenase A (LDHA), and decreased protein expression of HK2. 104 CEM-ADD cells exposed to dexamethasone for 48 hours followed by treatment for 72 hours with oligomycin, an inhibitor of ATP synthase, died in greater numbers than untreated cells and cells exposed to either agent alone.…”
Section: Figurementioning
confidence: 99%